Brucella spp. in equines slaughtered in the south region of Brazil - Santos, R. F. [UNESP]; Silva, G. C.P. [UNESP]; Assis, N. A. [UNESP]; Mathias, L. A. [UNESP] (FapUNIFESP (SciELO), 2016)
Bacteria of the genus Brucella are widespread in many countries. These microorganisms can infect humans and many wild and domestic animal species. These bacteria have zoonotic potential, and can cause economic and public health problems since they can be transmitted by direct contact with sick animals, through consumption of contaminated milk, raw meat and its derivatives (Soares et al., 2015). Brucellosis is considered a chronic evolving disease, unusual in horses, predominantly caused by Brucella abortus. However, it is not characterized by reproductive disorders in horses, but primarily by abscess in the cervical region, bursa, tendons, and joints. Transmission is likely to occur via ingestion of contaminated water and pastures, especially in areas endemic for bovine brucellosis (Ribeiro et al., 2008). The slaughterhouse is a strategic point for obtaining information about the animal and animal products, edible or not. This study investigated the presence of anti-Brucella spp. immunoglobulins in the serum samples from horses slaughtered in a slaughterhouse in southern Brazil, to estimate the frequency of Brucella spp. antibodies and determine the spatial distribution of the cases.
Keywords: Abattoirs; Brucellosis; Complement fixation; Equine; Fluorescence polarization